The Essentials of deceit: Postmodern reading of The Importance of Being Earnest by Oscar Wilde - Baskota, Dhananjaya (Damak Campus Journal, 2025)
The society and its dimensions change; however, some basic natures never change. Deceit has pervaded every society over the ages; and no sarcastically we claim, it has become essential. This paper explores Oscar Wilde’s The Importance of Being Earnest (1895) through a novelty approach of reading the text, i.e. postmodernist lens, focusing on the concepts of fraud and cheating, rather than displaying just absolute deception as a moral degradation. Wilde, through this play, satirizes Victorian norms and values, and illustrates the fluidity of truth and essential identity which prevails in the human mind. Employing theoretical frameworks from Lyotard (1979) and Baudrillard (1981), this study finds out that duplicity operates not only as comic consolation but also as a critique of essentialist values in this play. Using qualitative textual analysis, this article tries to explore how postmodern thought such as simulation, irony, uncertainty of truth, unstable meaning and performativity are assimilated in Wilde’s work in different dimensions.